PENGARUH LITERASI HALAL DAN RELIGIOSITAS TERHADAP KONSUMSI PRODUK HALAL PADA MAHASISWA MKS UIN SUNAN GUNUNG DJATI BANDUNG - Dinar Bagja Pratama; Neneng Hartati (UIN Sunan Gunung Djati Bandung, 2020)
Various factors are considered against the background of a Muslim in buying halal products, some of which is the level of student literacy and religiosity. The purpose of this study was to determine the effect of Halal Literacy and Religiosity on the consumption of halal products for UIN Bandung students. The method used in this research is the survey method and a quantitative approach. The population used is students of MKS UIN Bandung class of 2017 and a sample of 100 respondents was obtained. The research data uses primary data obtained from the research questionnaire. With multiple regression data analysis, the results showed that partially and simultaneously halal literacy and religiosity have a significant influence on the consumption of halal products in MKS UIN Bandung students. Halal literacy and religiosity have a very strong correlation with the consumption of halal products and are able to contribute an impact of 80,7% on the consumption of halal products.